Answer:
Step-by-step explanation:
The quadratic formula for a equation of form
ax²+bx + c = 0 is
![x= \frac{-b +- \sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-b%20%2B-%20%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
For the first equation,
x²+3x-4=0,
we can match that up with the form
ax²+bx + c = 0
to get that
ax² = x²
divide both sides by x²
a=1
3x = bx
divide both sides by x
3 = b
-4 = c
. We can match this up because no constant multiplied by x could equal x² and no constant multiplied by another constant could equal x, so corresponding terms must match up.
Plugging our values into the equation, we get
![x= \frac{-3 +- \sqrt{3^2-4(1)(-4)} }{2(1)} \\= \frac{-3+-\sqrt{25} }{2} \\ = \frac{-3+-5}{2} \\= -8/2 or 2/2\\= -4 or 1](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-3%20%2B-%20%5Csqrt%7B3%5E2-4%281%29%28-4%29%7D%20%7D%7B2%281%29%7D%20%5C%5C%3D%20%5Cfrac%7B-3%2B-%5Csqrt%7B25%7D%20%7D%7B2%7D%20%5C%5C%20%3D%20%5Cfrac%7B-3%2B-5%7D%7B2%7D%20%5C%5C%3D%20-8%2F2%20or%202%2F2%5C%5C%3D%20%20-4%20or%201)
as our possible solutions
Plugging our values back into the equation, x²+3x-4=0, we see that both f(-4) and f(1) are equal to 0. Therefore, this has 2 real solutions.
Next, we have
x²+3x+4=0
Matching coefficients up, we can see that a = 1, b=3, and c=4. The quadratic equation is thus
![x= \frac{-3 +- \sqrt{3^2-4(1)(4)} }{2(1)}\\= \frac{-3 +- \sqrt{9-16} }{2}\\= \frac{-3 +- \sqrt{-7} }{2}\\](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B-3%20%2B-%20%5Csqrt%7B3%5E2-4%281%29%284%29%7D%20%7D%7B2%281%29%7D%5C%5C%3D%20%5Cfrac%7B-3%20%2B-%20%5Csqrt%7B9-16%7D%20%7D%7B2%7D%5C%5C%3D%20%5Cfrac%7B-3%20%2B-%20%5Csqrt%7B-7%7D%20%7D%7B2%7D%5C%5C)
Because √-7 is not a real number, this has no real solutions. However,
(-3 + √-7)/2 and (-3 - √-7)/2 are both possible complex solutions, so this has two complex solutions
Finally, for
4x² + 1= 4x,
we can start by subtracting 4x from both sides to maintain the desired form, resulting in
4x²-4x+1=0
Then, a=4, b=-4, and c=1, making our equation
![x=\frac{-(-4) +- \sqrt{(-4)^2-4(4)(1)} }{2(4)} \\= \frac{4+-\sqrt{16-16} }{8} \\= \frac{4+-0}{8} \\= 1/2](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-4%29%20%2B-%20%5Csqrt%7B%28-4%29%5E2-4%284%29%281%29%7D%20%7D%7B2%284%29%7D%20%5C%5C%3D%20%5Cfrac%7B4%2B-%5Csqrt%7B16-16%7D%20%7D%7B8%7D%20%5C%5C%3D%20%5Cfrac%7B4%2B-0%7D%7B8%7D%20%5C%5C%3D%201%2F2)
Plugging 1/2 into 4x²+1=4x, this works as the only solution. This equation has one real solution